2005
DOI: 10.1063/1.2093931
|View full text |Cite
|
Sign up to set email alerts
|

Basal plane dislocation-free epitaxy of silicon carbide

Abstract: Molten KOH etching was implemented on SiC substrates before growing epilayers on them. It was found that the creation of basal plane dislocation (BPD) etch pits on the substrates can greatly enhance the conversion of BPDs to threading edge dislocations during epitaxy, and thus low BPD density and BPD-free SiC epilayers are obtained by this method. The reason why BPD etch pits can promote the earlier conversion is discussed. The SiC epilayer growth by this method is very promising in overcoming forward voltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 9 publications
1
87
2
Order By: Relevance
“…Since E BPD is very close to E TED , 16 It is also demonstrated that the BPD to TED conversion can be enhanced by growth interruptions, 18,19 substrate KOH etching, [20][21][22] or epilayer post annealing. 23 For SiC bipolar power devices, it is required that the BPD to TED conversion occurs in an n + buffer layer (i.e., BPDs are buried in the n + buffer layer.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since E BPD is very close to E TED , 16 It is also demonstrated that the BPD to TED conversion can be enhanced by growth interruptions, 18,19 substrate KOH etching, [20][21][22] or epilayer post annealing. 23 For SiC bipolar power devices, it is required that the BPD to TED conversion occurs in an n + buffer layer (i.e., BPDs are buried in the n + buffer layer.)…”
mentioning
confidence: 99%
“…Also the conversion of a BPD to TED is energetically favorable as discussed in detail in a reference. 16 The ratio of elastic energy per unit growth length for a BPD (W BPD ) to that for a TED (W TED ) can be derived from the references 16,17 and written aswhere E BPD and E TED are the elastic energies per unit length of dislocation line for a BPD and a TED respectively, and β is the substrate off-axis angle (≤8 It is also demonstrated that the BPD to TED conversion can be enhanced by growth interruptions, 18,19 substrate KOH etching,[20][21][22] or epilayer post annealing. 23 For SiC bipolar power devices, it is required that the BPD to TED conversion occurs in an n + buffer layer (i.e., BPDs are buried in the n + buffer layer.)…”
mentioning
confidence: 99%
“…As mentioned above, the BPD density was 250 cm -2 when the etching time at growth temperature was 12 minutes. It has previously been reported [8] that the creation of BPD etch pits on the substrate surface after molten KOH etching, enhanced the conversion of BPD into TED during epitaxial growth, this effect also increases as the dimension of the BPD etch pits on the substrates became larger. It can thus be speculated that as the etching time increased, the BPD etch pits on the substrates became larger which facilitated the BPD to TED conversion.…”
Section: Resultsmentioning
confidence: 93%
“…3 BPDs are present in 4H-SiC substrates with a typical BPD density in the order of 10 4 cm À2 and are able to either propagate to the epitaxial layer or convert to threading edge dislocations (TEDs). [4][5][6] It has been reported that converted BPDs, i.e., TEDs in the epilayer, can be inclined about 20 from the crystallographic c-direction of the crystal. 7,8 Such inclined TEDs are also known as TED II and TED III dislocations and can be identified based on their visibility in x-ray topographs.…”
Section: Introductionmentioning
confidence: 99%